2002
DOI: 10.1095/biolreprod67.4.1080
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Carbonyl Reductase-Like 20β-Hydroxysteroid Dehydrogenase Shows Distinct Surge in Messenger RNA Expression During Natural and Gonadotropin-Induced Meiotic Maturation in Nile Tilapia1

Abstract: Meiotic maturation in fish is accomplished by maturation-inducing hormones. 17alpha,20beta-Dihydroxy-4-pregnen-3-one (17alpha,20beta-DP) was identified as the maturation-inducing hormone of several teleosts, including Nile tilapia. A cDNA encoding 20beta-hydroxysteroid dehydrogenase (20beta-HSD), the enzyme that converts 17alpha-hydroxyprogesterone to 17alpha,20beta-DP, was cloned from the ovarian follicle of Nile tilapia. Genomic Southern analysis indicated that 20beta-HSD probably exists as a single copy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…The low transcript levels of 20bhsd during final maturation and spawning in cod is in apparent contrast to some previous studies, which showed increasing expression during final maturation and spawning in other teleost species such as ayu (Plecoglossus altivelis), tilapia and rainbow trout (Nakamura et al, 2005;Senthilkumaran et al, 2002Senthilkumaran et al, , 2004Tanaka et al, 2002). On the other hand, (Bobe et al, 2003(Bobe et al, , 2004 did not find any changes in 20bhsd transcript levels in rainbow trout ovarian follicles during maturation and suggested involvement of other factors such as other enzymes or growth factors, and/or substrate availability.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The low transcript levels of 20bhsd during final maturation and spawning in cod is in apparent contrast to some previous studies, which showed increasing expression during final maturation and spawning in other teleost species such as ayu (Plecoglossus altivelis), tilapia and rainbow trout (Nakamura et al, 2005;Senthilkumaran et al, 2002Senthilkumaran et al, , 2004Tanaka et al, 2002). On the other hand, (Bobe et al, 2003(Bobe et al, , 2004 did not find any changes in 20bhsd transcript levels in rainbow trout ovarian follicles during maturation and suggested involvement of other factors such as other enzymes or growth factors, and/or substrate availability.…”
Section: Discussioncontrasting
confidence: 98%
“…This is in agreement with results reported in other species such as rainbow trout, tilapia and ayu (Nakamura et al, 2005;Senthilkumaran et al, 2002;Tanaka et al, 2002), where highest levels of 20bhsd transcripts were found in postovulatory follicles. Pinillos et al (2002) and Antonopoulou et al (2011) found that MIS plasma concentrations peaked two months after spawning in the tench (Tinca tinca) but, unlike the situation in huchen and carp (Miura et al, 2007), it was not correlated to onset of first meiosis.…”
Section: Discussionsupporting
confidence: 93%
“…Since the isolation of a cDNA encoding CR/20β-HSD from pig (4), many studies have targeted CR/20β-HSD orthologs as being responsible for maturation-inducing hormone (MIH) synthesis (7,(28)(29)(30)(31)(32). Some studies demonstrated weak 20β-HSD activity of CR/20β-HSD towards 17OHP (7,30), whilst others did not check its activity (28,29,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, partial amino acid sequences of the purified enzyme were determined, and a cDNA encoding the protein has been isolated and characterized (4). Using the pig 20β-HSD cDNA as a probe, an ortholog was also isolated from the ovarian cDNA library of rainbow trout (5), and homologs have been isolated in other teleost fish as well (6,7). These homologous genes have been categorized as monomeric carbonyl reductase genes, which encode enzymes that possess wide substrate specificity for carbonyl compounds and are known as carbonyl reductase-like 20β-HSD (CR/20β-HSD) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Tilapia is an economically important species for aquaculture and also an ideal model for studying fish gametogenesis because of the availability of monosex larvae and well-studied functions of DHP during gamete maturation (Senthilkumaran et al 2002, Zhou et al 2007). However, the role of DHP in spermatogenesis during sexual differentiation remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%